Finding lupus in the ANA haystack - David R Karp; Nancy J Olsen (Lupus Science and Medicine)
Diagnosis of SLE in early stages is challenging due to the heterogeneous nature of presenting symptoms and the poor performance metrics of the screening ANA test. Even the more specific double-stranded DNA autoantibody has relatively low predictive value in early disease. A consequence is delayed referral, with the likelihood that some patients have progression of disease prior to specialist evaluation. Tests that might fill this diagnostic gap are therefore needed. The AVISE Connective Tissue Disease Test that uses a multiplex approach to detect autoantibodies and cell-bound complement products has shown utility in distinguishing SLE from other rheumatological conditions. Whether it might be useful in early disease stages to predict progression is addressed in a recent study by Liang and colleagues, who tested clinic patients who had non-specific findings with the objective of determining whether AVISE could predict onset of SLE. While this test provided more useful prognostic information than other available diagnostics, it had relatively low sensitivity, suggesting that significant numbers of patients with preclinical SLE would be missed by this screening. The need remains for development of diagnostics with robust sensitivity and specificity in early disease that would also deliver prognostic information about risk for SLE. Such tests would have great value as a tool for primary providers to more efficiently triage ANA-positive patients for appropriate specialty evaluation.